Madurese Men's Sinden or Lengge's Resistance to Gender Construction - Setyawan, Fery Agus; Julijanti, Dinara Maya; Dartiningsih, Bani Eka (Universitas Medan Area, 2025)
Madurese Sandur's art is unique in that those who play the role of sinden or lengge' are men. On the other hand, in gender construction, the roles of men and women are divided. In the field of work, men must have masculine professions, and women must have feminine professions. Because of this construction, someone can experience gender bias. This study aims to describe the form of resistance of Madurese male sinden or lengge' to gender construction. The method used is qualitative with a phenomenological approach. In addition, this study technique uses observation, interviews, documentation, and literature studies. The results show that Madurese male lengge experience negative stereotypes, namely that male lengge' are considered transvestites and like women. The existence of these stereotypes causes male lengge' to resist. The resistance carried out is only to suppress feelings every time someone labels him as a transvestite. This shows that Madurese male lengge' carries out closed resistance. Open resistance is also carried out by showing the fame of male lengge'. They prove that being a lengge' is not easy, this is proven by the fact that there is no regeneration of male lengge' in the Madurese sandur art.